ANALISIS KUANTITATIF INFORMED CONSENT TINDAKAN SECTIO CAESAREA DI RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG PERIODE TRIWULAN IV TAHUN 2020 - Bajeng Nurul Widyaningrum; Destri Maya Rani; Ratna Ratna (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2021)
Background : The informed consent form is a determining factor for taking medical action.  Objective : The purpose of this study was to determine the number and percentage of completeness and incompleteness of filling out the informed consent form for sectio caesarea. Method : This study is a descriptive study with a cross sectional approach with a total sampling technique of sampling, with a total of 243 informed consent sheets for sectio caesarea. From this study, the results of the highest completeness of informed consent for sectio caesarea were in the patient identification component, the highest completeness was 243 with a percentage of 100%, the highest incompleteness was 26 with a percentage of 11%, the documentation component was correct, the highest completeness was 213 with a percentage of 88%, the highest incompleteness was 34 with a percentage of 14%, in the important reporting component the highest completeness level is 236 with a percentage of 97%, the highest incompleteness is 38 with a percentage of 16%, and in the authentication component the highest completeness number is 232 with a percentage of 96%, the highest incompleteness is 56 with a percentage of 23%. Conclusion : The conclusion of this study is that the number of completeness in filling out the medical record informed consent form at the Roemani Muhammadiyah Hospital Semarang in the fourth quarter of 2020 has not reached the MSS for medical records at the hospital. This is because the implementation of the medical record service system is not optimal.